The use of mobile phones in the extension and advisory service in Rwanda - Stokke, A.F. (2019)
Agriculture plays a crucial role in most developing countries in sub-Saharan Africa, as it has an essential impact on the economy, food security and poverty. Extension and advisory service (EAS) is established as an important tool to improve agricultural development. The service aims to improve the agricultural production, income and well-being to farmers. However, the EAS is criticised for its limited reach of farmers, top-down approaches and ineffectiveness. Mobile phones are seen as a useful tool to overcome the existing barriers of the EAS due to its rapid growth in developing countries. This thesis assesses the use of mobile phones in the extension and advisory service in Rwanda. It examines farmers and extension service providers experience towards the use of mobile phones as a communication tool within the service. The study also examines barriers that led to the exclusion of certain groups of farmers. This qualitative research is based on twenty semi-structured interviews with respectively fourteen farmers, three extension service providers, one communication officer and two researchers. This study also uses secondary data such as reports and policy documents from Rwanda and the InnovAfrica project to ensure triangulation. The study found that the use of mobile phones has strengthened the EAS in relation to accessibility of the service, timeliness, two-way communication, being demand-driven and costs. However, these improvements only affect farmers with access to a mobile phone and exclude groups of farmers due to poverty and traditional gender roles.